Pluteus keselakii (Pluteaceae, Agaricales), a new species in section Celluloderma - Ševčíková, Hana; Moreau, Pierre-Arthur; Borovička, Jan (Phytotaxa, 2020)
Pluteus keselakii, a new species in the section Celluloderma, is described and illustrated based on collections from Slovakia and France. Pluteus keselakii is characterised by a brown pileipellis largely composed of sphaeropedunculate to broadly clavate elements, a whitish stipe covered entirely by distinct brown floccules consisting of caulocystidia in tufts, narrowly utriform to utriform or fusiform pleurocystidia with obtuse apex and a brown lamella edge (at least near the pileus margin). Pluteus keselakii is macromorphologically similar to P. floccipes and phylogenetically (ITS rDNA) close to P. multiformis. The distinctive sequences of the ITS and EF1-α gene regions, however, support the status of P. keselakii as a new species.